Entry Deterrence, Divisionalization, and Investment Decisions - Veendorp, E. C. H. (Quarterly Journal of Economics, 1991)
Journal Article Entry Deterrence, Divisionalization, and Investment Decisions Get access E. C. H. Veendorp E. C. H. Veendorp Clark University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 106, Issue 1, February 1991, Pages 297–307, https://doi.org/10.2307/2937918 Published: 01 February 1991